Biological and Prognostic Significance of the Morphological Types and Vascular Patterns in Colorectal Liver Metastases (CRLM): Looking Beyond the Tumor Margin. Issue 8 (February 2016) - Siriwardana, Pulathis N.; Luong, Tu Vinh; Watkins, Jennifer; Turley, Helen; Ghazaley, Mohamed; Gatter, Kevin; Harris, Adrian L.; Hochhauser, Daniel; Davidson, Brian R.
Abstract : Abstract: Patients with encapsulated colorectal liver metastases (CRLM) have a better prognosis than those without a capsule. The reason for the encapsulation is unknown. Hypoxia inducible factor-1α (HIF-1α) increases tumor angiogenesis and tumor tissue expression is associated with reduced survival. Our aim was to determine whether the good prognosis of encapsulated CRLM is associated with reduced HIF-1α expression by the cancer. The study selected only patients who had not undergone neoadjuvant chemotherapy prior to a potentially curative hepatectomy for CRLM. From 30 selected patients, serial sections were cut from a single randomly selected metastasis. Morphology was assessed following H&E staining. Tumor hypoxia, vascular endothelial growth factor (VEGF), proliferation, and microvascular density (MVD) were assessed by immunostaining for HIF-1α and carbonic anhydrase-9 (CA-9), VEGF, Ki67, and cluster of differentiation-31, respectively. MVD was calculated in the vascular hot spots. Pathology was reported without clinical outcome information. Actual long-term survival was recorded. Thirteen (43%) of the cancers were encapsulated CRLM containing glands which were large, complex, and cribriform. Thirteen (43%) were infiltrative CRLM and their glands were small, closely packed, and rounded with vessels in the interglandular fibrous tissue with no capsule; 3 (10%) had a mixed picture. Encapsulated CRLM had a higher expression of HIF-1α (58% vs 8%, P  = 0.03), CA-9 (42% vs 0%, P  = 0.04), and VEGF (92% vs 25%, P  = 0.02). MVD was lower in the encapsulated CRLM group (37 mm 2 vs 143 mm 2, P  < 0.001). The median follow-up was 115 months. The encapsulated CRLM group had a better overall and 5-year survival (relative hazard: 0.58, P  = 0.057 and hazard ratio: 0.52, P = 0.044). There are 2 main morphological appearances of CRLM which have very different long-term survival following liver resection surgery. The morphology is associated with differences in expression of HIF-1α, CA-9, VEGF, and angiogenesis.